2007
DOI: 10.1071/rd07037
|View full text |Cite
|
Sign up to set email alerts
|

Applications and interpretation of computer-assisted sperm analyses and sperm sorting methods in assisted breeding and comparative research

Abstract: Theoretical and practical knowledge of sperm function is an essential requirement in almost every aspect of modern reproductive technology, if the overarching objective is the eventual production of live offspring. Artificial insemination (AI) techniques depend on the availability of high quality semen, whether fresh, diluted and stored, or frozen. Assessing such semen for quality and the likelihood of fertility is therefore also important, as much time, resources and effort can easily be wasted by using poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 68 publications
3
52
1
6
Order By: Relevance
“…Modern estimates of sperm motility in mammals, made for the purposes of quality control or fertility prediction, use optical or laser-tracking technology to analyse cell movement within a semen sample diluted in a physiological medium [1][2][3]. Although such an in vitro approach is valuable in both a human and veterinary context, it fails to take account of the varied conditions encountered by a sperm cell during passage along the female tract.…”
Section: Introductionmentioning
confidence: 99%
“…Modern estimates of sperm motility in mammals, made for the purposes of quality control or fertility prediction, use optical or laser-tracking technology to analyse cell movement within a semen sample diluted in a physiological medium [1][2][3]. Although such an in vitro approach is valuable in both a human and veterinary context, it fails to take account of the varied conditions encountered by a sperm cell during passage along the female tract.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we aimed at taking 76 into account the within-sample heterogeneity that CASA data conveys, using the median values (not the 77 means, very sensitive to extreme values) for studying more reliably the kinematic parameters. 78Moreover, we have taken advantage of the potential of CASA data (Holt et al, 2007), classifying 79 the spermatozoa within each sample according to their kinematic characteristics. This requires 80 multivariate techniques such as cluster analysis (Martínez-Pastor et al, 2011).…”
mentioning
confidence: 99%
“…CASA provides rapid, precise and validated objective sperm motion characteristics and has been applied in our laboratory for ram lamb semen (Kumar et al, 2010). Developments in CASA technique have shown that it provides powerful insights into sperm function and semen heterogeneity (Holt et al, 2007). Sperm velocity and motility are among the most important essential parameters in the examination of sperm quality and in the establishment of a correlation between sperm quality and fertility (Vestergen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%